A Pilot Feasibility Study of Yttrium‐90 Liver Radioembolization Followed by Durvalumab and Tremelimumab in Patients with Microsatellite Stable Colorectal Cancer Liver Metastases. (19th December 2019) - Wang, Chongkai; Park, John; Ouyang, Ching; Longmate, Jeff A.; Tajon, Michael; Chao, Joseph; Lim, Dean; Sandhu, Jaideep; Yin, Hongwei Holly; Pillai, Raju; Gozo, Maricel C.; Avalos, Christian; et al.
Abstract: Trial Information : ClinicalTrials.gov Identifier: NCT03005002 Sponsor : AstraZeneca Principal Investigator : Marwan Fakih IRB Approved : Yes Click here to access other published clinical trials . Lessons Learned : Radioembolization with yttrium‐90 resin microspheres can be combined safely with full doses of durvalumab and tremelimumab in patients with metastatic colorectal cancer. Regional radioembolization with yttrium‐90 resin microspheres did not result in any hepatic or extrahepatic responses to a combination of durvalumab and tremelimumab. The lack of immunomodulatory responses to yttrium‐90 on biopsies before and after treatment rules out a potential role for this strategy in converting a "cold tumor" into an "inflamed, " immune responsive tumor. Background: PD‐1 inhibitors have been ineffective in microsatellite stable (MSS) metastatic colorectal cancer (CRC). Preclinical models suggest that radiation therapy may sensitize MSS CRC to PD‐1 blockade. Methods: Patients with MSS metastatic CRC with liver‐predominant disease who progressed following at least one prior line of treatment were treated with yttrium‐90 (Y90) radioembolization to the liver (SIR‐Spheres; Sirtex, Woburn, MA) followed 2–3 weeks later by the combination of durvalumab and tremelimumab. A Simon two‐stage design was implemented, with a planned expansion to 18 patients if at least one response was noted in the first nine patients. Results: Nine patients enrolled in the first stage of the study, all with progressive disease (PD) during or after their first two cycles of treatment. Per preplanned design, the study was closed because of futility. No treatment‐related grade 3 or greater toxicities were recorded. Correlative studies with tumor biopsies showed low levels of tumor‐infiltrating lymphocyte (TIL) infiltration in tumor cancer islands before and after Y90 radioembolization. Conclusion: Y90 radioembolization can be added safely to durvalumab and tremelimumab but did not promote tumor‐directed immune responses against liver‐metastasized MSS CRC.